Singapore makes its mark with the Tour de France - Milhiet, Paco (2024)
The third edition of the Tour de France Prudential Singapore Criterium took place on November 9-10, 2024. Over the years, the Tour de France, the world’s most prestigious cycling race, has evolved into a powerful instrument of soft power, taking on geopolitical significance, building cultural bridges and fostering mutual economic benefits. Underlining the establishment of a regular Singapore Criterium stage in the Tour de France is an ambition to strengthen the premier event’s presence and appeal in Southeast Asia. For Singapore, it strengthens its reputation as a venue for major sporting events.